Phenomenological research methods - Moustakas, Clark (Thousand Oaks Sage Publications, 1994)
In this volume, Clark Moustakas clearly discusses the theoretical underpinnings of phenomenology, based on the work of Husserl and others, and takes the reader step-by-step through the process of conducting a phenomenological study. His concise guide provides numerous examples of successful phenomenological studies from a variety of fields including therapy, health care, victimology, psychology and gender studies. The book also includes form letters and other research tools to use in designing and conducting a study.